Francisella novicida Mutant XWK4 Triggers Robust Inflammasome Activation Favoring Infection - Guo, Yu; Mao, Rudi; Xie, Qingqing; Cheng, Xiaojie; Xu, Tao; Wang, Xiaoyuan; Du, Yan; Qi, Xiaopeng (Frontiers in Cell and Developmental Biology, 2021)
Bacterial infection tendentiously triggers inflammasome activation, whereas the roles of inflammasome activation in host defense against diverse infections remain unclear. Here we identified an ASC-dependent inflammasome activation played opposite roles in host defense against Francisella novicida WT U112 and mutant strain XWK4. Comparing with U112, XWK4 infection induced robust cytokine production, ASC-dependent inflammasome activation and pyroptosis. Both AIM2 and NLRP3 were involved and played redundant roles in XWK4-induced inflammasome activation. Type II but not type I interferon was partially required for XWK4-triggered inflammasome activation, which was different from type I interferon dependency in U112-induced inflammasome activation. Distinct from Francisella novicida U112 and Acinetobacter baumannii infection, Asc–/– mice were more resistant than WT mice response to XWK4 infection by limiting bacterial burden in vivo. The excessive inflammasome activation triggered by XWK4 infection caused dramatical cell death and pathological damage. Our study offers novel insights into mechanisms of inflammasome activation in host defense and provides potential therapeutic approach against bacterial infections and inflammatory diseases.